2015
DOI: 10.1038/srep14817
|View full text |Cite
|
Sign up to set email alerts
|

Co-doping of Ag into Mn:ZnSe Quantum Dots: Giving Optical Filtering effect with Improved Monochromaticity

Abstract: In optics, when polychromatic light is filtered by an optical filter, the monochromaticity of the light can be improved. In this work, we reported that Ag dopant atoms could be used as an optical filter for nanosized Mn:ZnSe quantum dots (QDs). If no Ag doping, aqueous Mn:ZnSe QDs have low monochromaticity due to coexisting of strong ZnSe band gap emission, ZnSe trap emission, and Mn dopant emission. After doping of Ag into QDs, ZnSe band gap and ZnSe trap emissions can be filtered, leaving only Mn dopant emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…The inert nature of the glass matrix guarantees the photo-chemical and thermal stability of QDs embedded inside 20 21 22 , prevents the agglomeration of QDs and provides access to device fabrication 6 . In fact, II-VI QDs doped glasses have been widely used in optical filters 23 24 and recent studies have shown their great potentials in luminescent devices, such as LED color converters and other optical emitters 25 26 .…”
mentioning
confidence: 99%
“…The inert nature of the glass matrix guarantees the photo-chemical and thermal stability of QDs embedded inside 20 21 22 , prevents the agglomeration of QDs and provides access to device fabrication 6 . In fact, II-VI QDs doped glasses have been widely used in optical filters 23 24 and recent studies have shown their great potentials in luminescent devices, such as LED color converters and other optical emitters 25 26 .…”
mentioning
confidence: 99%
“…The result was similar to PL decay in Mn 2+ : ZnSe and Mn 2+ :CdS/ZnS nano-crystals as reported earlier. 24,25 However, for more than 5% Mn 2+ doping, the PL decay curve could be tted well with a biexponential function.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the complex synthesis process and expensive phosphine precursor are needed upon preparation of InP based NCs 18 25 26 . For Mn 2+ d-NCs, the dopant emission is restricted to the orange-red region because the emission comes from the intrinsic 4 T 1 – 6 A 1 transition of Mn 2+ which is relatively independent of the nature and size of host NCs 12 14 27 28 29 . As to Cu or Ag d-NCs, the dopant emission can be tuned by simply controlling the size of host NCs, resulting in a narrow and tunable emission window from blue to green 6 9 11 30 31 32 .…”
mentioning
confidence: 99%